Free hearts and free homes : gender and American antislavery politics - Pierson, Michael D. (Gender & American culture., 2003)
By exploring the intersection of gender and politics in the antebellum North, Michael Pierson examines how antislavery political parties capitalized on the emerging family practices and ideologies that accompanied the market revolution.